Teologi Ekonomi Islam; Kontruksi Prinsip Ilahiyah menuju Aktualisasi Bermuamalah - Anzaikhan, M.; Nasir, Muhammad; Zulkarnaen, Zulkarnaen; Drajat, Amroini; Rafiqah, Rafiqah; Umam, Chatibul (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This article aims to examine the construction of divine principles in realizing the actualization of muamalah (Islamic economic transactions) in accordance with the theological values of Islamic economics, as a solution to modern economic problems that are laden with social inequality, individualism, and market exploitation. The benefit of this research is to contribute to the development of economic practices that are not solely profit-oriented but also emphasize social welfare and economic sustainability. This article is categorized as field research with a qualitative approach, using a descriptive-analytical study as its methodology. The results conclude that economic theology is not merely a normative study discussing the relationship between humans and God but also serves as a fundamental basis for building spiritual awareness in muamalah activities. The construction of divine principles becomes a key pillar in shaping fair, transparent, and community-oriented muamalah, as well as offering a resolution to the distortions of the modern economic system.